Hubungan Beban Kerja Dengan Stres Kerja Pada Karyawan SPPBE PT. Mitha Sarana Wijaya - Toto Haraventa; Findy Suri (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
This study aims to determine the corellation between workload and work stress on employees of SPPBE PT. Mitha Sarana Wijaya. The problem that is focused on this research is to determine the corellation between workload and work stress on employees of SPPBE PT. Mitha Sarana Wijaya in the Filling Hall area. The hypothesis proposed is that there is a positive corellation between workload and work stress for SPPBE employees in the Filling Hall area, meaning that the higher the workload, the higher the work stress. Conversely, the lower the workload of employees, the lower the work stress. The sample in this study were 32 employees of PT. Mitha Sarana Wijaya. The sampling technique in this study is a total sampling technique. The method used in this study is a quantitative method. The form of the scale in this study is a Likert scale. To approach this problem, the theoretical reference is used from the workload aspect according to Tarwaka (2011) and the work stress aspect according to Robbin (2006). In this study, there are two scales, namely the workload scale and the work stress scale. with the coefficient of workload reliability with the Cronbach Alpha formula 0.954 and the work stress reliability coefficient with the Cronbach Alpha formula 0.911. Data analysis using product moment correlation. Based on data analysis, there is a significant relationship between workload and employee work stress (rxy = 0.493; P = 0.004 0.05). Furthermore, it is known that the contribution of workload to work stress on employees is 24.3% while 75.7% is influenced by other factors. It is known that the workload is classified as high where the hypothetical mean is 75 from the empirical mean 92.84 and the difference exceeds the SD value of 16,760. And work stress is also high where the hypothetical mean is 72.5 from the empirical mean 95.41 and the difference exceeds the SD value of 12.735